2021
DOI: 10.1039/d1ra01943k
|View full text |Cite
|
Sign up to set email alerts
|

Rhododendron and Japanese Knotweed: invasive species as innovative crops for second generation biofuels for the ionoSolv process

Abstract: Japanese Knotweed (Fallopia japonica) and Rhododendron (Rhododendron ponticum), two invasive species in the UK that are an environmental threat and economic burden, can be integrated into a flexible ionic liquid based biorefinery process to produce bioenergy and chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…[53][54][55] The pretreatment conditions of the biomass were set at 150°C for 1 hour, given the lignin content is of Miscanthus as displayed in Figure 2 (a) and previous studies carried out on various lignocellulosic feedstocks for the ionoSolv process. 25,56,57 shows that the ionoSolv pretreatment was able to produce a cellulose-rich pulp, with 84 % glucan recovery, while removing 97.5 % of the hemicelluloses and 60 % of lignin. This deconstruction of the biomass from the ionic liquid pretreatment enabled 81.5 % of the theoretical maximum of glucose to be released through enzymatic saccharification of the pulp, a 3.8 fold increase compared to saccharification of the untreated (raw) samples of the feedstock.…”
Section: Fractionation Of Biomass Using [H1cim]clmentioning
confidence: 99%
See 2 more Smart Citations
“…[53][54][55] The pretreatment conditions of the biomass were set at 150°C for 1 hour, given the lignin content is of Miscanthus as displayed in Figure 2 (a) and previous studies carried out on various lignocellulosic feedstocks for the ionoSolv process. 25,56,57 shows that the ionoSolv pretreatment was able to produce a cellulose-rich pulp, with 84 % glucan recovery, while removing 97.5 % of the hemicelluloses and 60 % of lignin. This deconstruction of the biomass from the ionic liquid pretreatment enabled 81.5 % of the theoretical maximum of glucose to be released through enzymatic saccharification of the pulp, a 3.8 fold increase compared to saccharification of the untreated (raw) samples of the feedstock.…”
Section: Fractionation Of Biomass Using [H1cim]clmentioning
confidence: 99%
“…Lignin is often valorised for its energy value as a fuel, and the molecular changes and higher heating value of ionoSolv lignin have been studied elsewhere. 25,58,59 Despite lignin being a potential absorbent for metals, the metal preferably remained in the [H1Cim]Cl liquor, and in the pulp to a lesser extent. 60,61 The metal extraction from the ionic liquid occurs during the pretreatment at high temperature, where some metal (Fe, As, Ni, Cr) remain or redeposited onto the pulp.…”
Section: Fractionation Of Biomass Using [H1cim]clmentioning
confidence: 99%
See 1 more Smart Citation
“…Feedstock-agnostic pretreatment can utilize a wide array of biomass feedstocks, liberating a high yield of the monosaccharides and lignin-derived phenolic intermediates. Several studies revealed that some ILs and DESs exhibited versatility with multiple feedstocks with high pretreatment efficiency (Hennequin et al, 2021). A relatively high capability of ILs and DESs for the dissolution of biomass components makes them promising pretreatment reagents.…”
Section: Feedstock-agnostic Solventmentioning
confidence: 99%
“…For example, thermochemical processes such as pyrolysis and gasification are more robust to feedstock type, 7 and the use of ionic liquids (ILs) affords fractionation for hardwoods, softwoods, herbaceous dicots, and monocots. 8–10…”
Section: Introductionmentioning
confidence: 99%